2023
DOI: 10.3389/fbioe.2023.1171908
|View full text |Cite
|
Sign up to set email alerts
|

Inspired by nature: Fiber networks functionalized with tannic acid and condensed tannin-rich extracts of Norway spruce bark show antimicrobial efficacy

Abstract: This study demonstrated the antibacterial and antiviral potential of condensed tannins and tannic acid when incorporated into fiber networks tested for functional material purposes. Condensed tannins were extracted from industrial bark of Norway spruce by using pressurized hot water extraction (PHWE), followed by purification of extracts by using XADHP7 treatment to obtain sugar-free extract. The chemical composition of the extracts was analyzed by using HPLC, GC‒MS and UHPLC after thiolytic degradation. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Also, TA containing nanoparticles have been shown to induce antiviral activity ( Orłowski et al, 2018 ). Furthermore, in our previous study, TA also showed efficacy against CVB3 when it was bound to handsheets using a dip coating method without any additional binding polymers or chemicals ( Jyske et al, 2023 ). Although in that study, TA was not strongly bound to the surface and probably efficacy was based on easily leaching TA from the surface, TA showed its promise also against the stable enteroviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, TA containing nanoparticles have been shown to induce antiviral activity ( Orłowski et al, 2018 ). Furthermore, in our previous study, TA also showed efficacy against CVB3 when it was bound to handsheets using a dip coating method without any additional binding polymers or chemicals ( Jyske et al, 2023 ). Although in that study, TA was not strongly bound to the surface and probably efficacy was based on easily leaching TA from the surface, TA showed its promise also against the stable enteroviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Industrial Norway spruce [ P. abies (L.) Karst.] bark from a sawmill was retrieved and extracted as described previously ( Jyske et al, 2023 ). Willow (Salix spp.)…”
Section: Methodsmentioning
confidence: 99%
“…19 Spruce tannin, supplied by LUKE (Helsinki, Finland), was obtained by hot water extraction of spruce bark followed by purification using the XAD7HP adsorbent. 28,29 The spruce tannin was referred to as crude tannin. Comprehensive information regarding the manufacturing, purification, and fractionation processes of lignin and tannin is available in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The authors also reported that their coatings must be developed to ensure a long-term antibacterial effect since the noncovalent bonds were the driving force between TA and the handsheet substrate. 30 As a result, the durability of zwitterionic polymer-based coating is a challenge during large-scale application, even when the polymer was covalently linked to TA. 31 In this work, we report a simple one-pot dip-coating process for depositing TA and zwitterionic copolymers containing amine groups under oxidizing conditions to form covalent conjugation between the quinone and amino groups via the Michael addition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…coli, and Enterovirus coxsackievirus. The authors also reported that their coatings must be developed to ensure a long-term antibacterial effect since the noncovalent bonds were the driving force between TA and the handsheet substrate . As a result, the durability of zwitterionic polymer-based coating is a challenge during large-scale application, even when the polymer was covalently linked to TA …”
Section: Introductionmentioning
confidence: 99%